Argentina's countercyclical credit policy response: macroprudential regulation and public bank credit during Covid-19 - Schclarek Curutchet, Alfredo (United Nations Trade and Development (UNCTAD), 2024)
Fil: Schclarek Curutchet, Alfredo. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.